Pemikiran Tuan Guru Dato Hj Nik Abdul Aziz Nik Mat dalam Ekonomi - Hasan, Surtahman Kastin; Ahmad, Norfadzilah (Jurnal Usuluddin, 2004)
Study of economic thought of Dato Hj Nik Abdul Aziz will cover not only the material aspect, but also the inner aspect of Islam i.e. spiritual. He promotes ethical values in his administration: moderation in lifestyle and careful government spending. His views on development, poverty, riba and gambling are in accordance to the general view of Islamic economists.